Peculiarities of pumpkin carotenoid composition ‘Konfetka’ variety, prospects of utilization - N. A. Golubkina; G. A. Khimich; M. S. Antoshkina; U. D. Plotnikova; S. M. Nadezhkin; I. B. Korottseva (Овощи России, 2021)
Relevance. Pumpkin is one of the most important source of carotenoids for humans: β- and α-carotene, lutein and zeaxanthin playing a fundamental role in providing twilight and color vision accordingly.Results. Investigation of pumpkin carotenoid composition, Konfetka variety, revealed for the first time that this cultivar is the only one containing exclusively lutein in pulp with lutein and zeaxanthin in peel and lutein, zeaxanthin and β-carotene in placenta. Lutein concentration in pulp reached 11 mg/100 g, peel – 41.3/100 g, placenta – 51.2 mg/100 g. Zeaxanthin was absent in pulp and reached 28.3 mg/100 g in peel, and 10 mg/100 g in placenta. β-Carotene was detected only in placenta where its concentration was as much as 94.7 mg/100 g. The results indicate great prospects of ‘Konfetka’ components utilization (pulp, peel, placenta) in food industry, production of baby food and biologically active food additives, containing lutein and zeaxanthin.